2008
DOI: 10.1113/jphysiol.2008.154971
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models of human KCNQ2 and KCNQ3 mutations for benign familial neonatal convulsions show seizures and neuronal plasticity without synaptic reorganization

Abstract: The childhood epilepsy syndrome of benign familial neonatal convulsions (BFNC) exhibits the remarkable feature of clinical remission within a few weeks of onset and a favourable prognosis, sparing cognitive abilities despite persistent expression of the mutant KCNQ2 or KCNQ3 potassium channels throughout adulthood. To better understand such dynamic neuroprotective plasticity within the developing brain, we introduced missense mutations that underlie human BFNC into the orthologous murine Kcnq2 (Kv7.2) and Kcnq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
108
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 38 publications
13
108
1
Order By: Relevance
“…They include autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) [7][8][9], benign familial neonatal convulsion (BFNC) [10,11], childhood absence epilepsy (CAE) [12,13], severe myoclonic epilepsy in infancy (SMEI) [14] and febrile seizures (FS) [15]. However, their phenotypic features have not been determined fully.…”
Section: Introductionmentioning
confidence: 99%
“…They include autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) [7][8][9], benign familial neonatal convulsion (BFNC) [10,11], childhood absence epilepsy (CAE) [12,13], severe myoclonic epilepsy in infancy (SMEI) [14] and febrile seizures (FS) [15]. However, their phenotypic features have not been determined fully.…”
Section: Introductionmentioning
confidence: 99%
“…5 Soh et al extended these findings by showing that deletion of Kcnq2-but not Kcnq3-from cortical pyramidal neurons is sufficient for the development of aberrant EEG activity and leads to death by the third week of life. Electrophysiological recordings from pyramidal neurons in the CA1 subregion of the hippocampus showed that in the absence of KCNQ2 channels the M-current was reduced by »85%, whereas the mAHP was reduced by »50-60%.…”
mentioning
confidence: 68%
“…Transgenic mice expressing a dominant negative KCNQ2 mutant [59] show spontaneous partial and generalized tonicclonic seizures, but also pronounced hyperactivity and cell loss in the hippocampus, with impaired hippocampus-related memory, which are not consistent with the typical BNFS human phenotype. Knockin mice of KCNQ2 A306T and KV7.3 G311V mutations [60] show spontaneous tonic-clonic seizures and, consistent with BNFS, no hippocampal neurodegeneration; however, only homozygous mice manifest epilepsy, and they also tend to have seizures in adulthood.…”
Section: Spectrum Of Benign Epilepsies In Newborns and Infantsmentioning
confidence: 99%